Engineering protein assemblies with allosteric control via monomer fold-switching - Luis A. Campos (Nature Portfolio, 2019)
The design of protein assemblies is a major thrust for biomolecular engineering and nanobiotechnology. Here the authors demonstrate a general mechanism for designing allosteric macromolecular assemblies and showcase a proof of concept for engineered allosteric protein assembly.